Business Cases and Corporate Engagement with Sustainability: Differentiating Ethical Motivations - Schaltegger, Stefan (Journal of business ethics, 2018)
This paper explores links between different ethical motivations and kinds of corporate social responsibility (CSR) activities to distinguish between different types of business cases with regard to sustainability. The design of CSR and corporate sustainability can be based on different ethical foundations and motivations. This paper draws on the framework of Roberts (Organization 10:249–265, 2003) which distinguishes four different ethical management versions of CSR. The first two ethical motivations are driven either by a reactionary concern for the short-term financial interests of the business, or reputational, driven by a narcissistic concern to protect the firm’s image. The third responsible motivation works from the inside-out and seeks to embed social and environmental concerns within the firm’s performance management systems, and the fourth, a collaborative motivation, works to bring the outside in and seeks to go beyond the boundaries of the firm to create a dialogue with those who are vulnerable to the unintended consequences of corporate conduct. Management activities based on these different ethical motivations to CSR and sustainability result in different operational activities for corporations working towards sustainability and thus have very different effects on how the company’s economic performance is influenced. Assuming that corporate managers are concerned about creating business cases for their companies to survive and prosper in the long term, this paper raises the question of how different ethical motivations for designing CSR and corporate sustainability relate to the creation of different business cases. The paper concludes by distinguishing four different kinds of business cases with regard to sustainability: reactionary and reputational business cases of sustainability, and responsible and collaborative business cases for sustainability.